Suplementação de colina em dietas para poedeiras - Roberta Juliana Costa Vasconcelos (2013)
In order to evaluate the effect of supplementation levels of choline in diets for laying hens on performance, internal and external quality of eggs and macro and microscopic analysis of livers an experiment was conducted in two phases. In the first phase was to study the effect of choline supplementation on the performance of one to 14 weeks of age. We used 2240 pullets Dekalb White, housed in a shelter conventional. The experimental design was completely randomized design with two treatments and 14 repetitions of 80 birds per experimental unit. Diets isonutrient, except the levels of choline. The treatments were defined by the levels of choline supplementation. There was no difference between treatments (p> 0.05), F test, the body weight, feed intake, feed conversion and viability, or for the macro and microscopic features of liver by the Mann-Whitney. In the second phase, the effect of the levels of choline supplementation on broiler performance, macro and microscopic analysis of livers of poultry and egg quality during production. 1800 birds were used in the 18 weeks of age from phase I. The experimental design was completely randomized in a factorial 2x5 (two levels of choline supplementation phases: initial and re-x five levels of choline supplementation on laying phase) with six replicates of 30 birds each. Diets isonutrient, except the levels of choline. The treatments were defined by the levels of choline supplementation. There was no difference between treatments (p> 0.05), F test, as the feed and the number of eggs per bird housed. The daily egg production was observed interaction of choline supplementation in the growing phase, with levels of choline in the production phase (p 0.05). Positive linear effect was obtained when the diets were supplemented with choline in the growing phase, when it was made to supplement this phase, there was a linear effect. The weight of the birds, feed intake and viability there was no interaction (p 0.05). For macroscopic and microscopic evaluation of liver phase I, the design was completely randomized design with two treatments (with and without choline supplementation) with eight replications, each bird was considered a recurrence. For macroscopic and microscopic evaluations of the livers of the experimental phase II was randomized in a factorial 2x5 (2 levels of choline supplementation phases: initial and re-x 5 levels of choline supplementation on laying phase) with four replications , and each liver was considered as a repetition. There was no statistical difference (p> 0.05) for any variable. For the evaluation of the quality of the eggs was the same design used for the benchmarks, except for the number of replications was 30, and each egg was considered as one repetition. There was no interaction between choline supplementation in growing and choline levels in the laying stage for any of the variables observed, except the percentage of shell.